Monitoring seating interface pressure in wheelchair sports - Lewis, A. R.; Haydon, D. S.; Phillips, E. J.; Grimshaw, P. N.; Robertson, W. S. P.; Portus, M. (Sports Engineering, 2018)
A robust method of quantifying athlete movement and pressure distribution across the seating interface of wheelchair athletes is required for athlete monitoring, optimising athlete performance, and computational simulations. The purpose of this study was to investigate whether a pressure mat is capable of measuring the distribution of pressure during wheelchair sport motion, and analyse the relationship between an athlete`s pressure distribution and their movement at the seating interface. Pressure was measured at the seating interface (wheelchair racing, n = 6, wheelchair rugby, n = 2) under conditions of steady state (racing athletes only), acceleration from stationary (racing and rugby), and agility (rugby only). All athletes demonstrated large within-trial variation in average pressure, peak pressure, and contact area for the acceleration and agility (rugby only) trials, suggesting the change in requirements of the seating interface for wheelchair athletes across different motions. This research suggests the need for greater individualisation of athlete-wheelchair seating interfaces to promote performance, as well as the importance of including these seating interactions in biomechanical analyses of wheelchair propulsion. Regular monitoring of pressure distribution and sport specific demands will assist in wheelchair prescription and provide improved understanding of individual seat design requirements associated with specific athlete impairments.